The Effects of Time Limits, the EITC, and Other Policy Changes on Welfare Use, Work, and Income among Female-Headed Families - Grogger, Jeffrey (The Review of Economics and Statistics, 2003)
Of all of the welfare reforms that were implemented during the 1990s, time limits may represent the single greatest break from past policy. This paper expands on what is known about this important welfare reform measure by exploiting the predictions from Grogger and Michalopoulos (2003) to estimate the effects of time limits on welfare use, employment, labor supply, earnings, and income among female-headed families. Results based on data from the March Current Population Survey suggest that time limits have had important effects on welfare use and work, accounting for about one-eighth of the decline in welfare use and about 7% of the rise in employment since 1993. They have had no significant effect on earnings or income, however. The analysis also shows that the collective effects of other reforms have had important impacts on employment and labor supply. Furthermore, it identifies the Earned Income Tax Credit (EITC) as a particularly important contributor to both the recent decrease in welfare use and the recent increase in employment, labor supply, and earnings.